La curva de rendimientos como reflejo de las expectativas inflacionarias en Colombia (2003-2020) (2021)
In this work, through a statistical analysis, inflationary expectations were extracted from the yield curve of public debt bonds between 2002 and 2020 and it was verified, to what extent, it is aligned with the expectations of market agents. At the same time, an analysis is carried out that allows us to recognize that inflation expectations surveys are the most efficient inflation expectations metric when it comes to predicting effective inflation. Finally, emphasis is placed on the elements that affect the behavior of the variables related to the spread between the inflation expectations and observed inflation metrics.